Набуття корпоративних прав одним із подружжя - Вінтоняк, Наталія Дмитрівна; Vintonya, Nataliia (ВД "Гельветика", 2019)
Статтю присвячено дослідженню правового регулювання корпоративних прав подружжя, набутих одним із подружжя за рахунок майна, що належить подружжю на праві спільної сумісної власності. Розглянуто внесення майна, що належить подружжю на праві спільної сумісної власності, як вкладу до статутного капіталу юридичної особи корпоративного типу, як первісний спосіб набуття корпоративних прав, та укладення цивільно-правових договорів – як похідний. Приділено увагу згоді подружжя під час набуття корпоративних прав одним із подружжя.

The paper examines the issues of the legal regulation of spouses’ corporate rights acquired by one of the spouses by means of marital property. The two ways of acquiring corporate rights have been discussed, namely investing marital property into the authorized share capital of a corporation as a primary way, and entering into civil agreements as a derivative way. The issues regarding the acquisition of corporate rights by one of the spouses by means of investing marital property into the authorized share capital of a corporation without the other spouse’s consent become more relevant in the dispute resolution practice. Consequently, this paper is aimed at finding ways to resolve the mentioned above issue by way of paying close attention to spousal consent. Clear and unambiguous definition of spousal consent will help to avoid the violation and abuse of rights of either spouse. It has been investigated that in case one of the spouses invests marital property into the authorized share capital of a corporation on the stage of its incorporation as a predetermined contribution, then it is believed that such act implies mutual consent. In other words, it is presumed consent. Since the moment marriage is registered, any acts by either spouse pursuant to the right to dispose of the property (marital property, in this instance) are deemed to be performed by mutual consent, including investing marital property into authorized share capital of a corporation. It has been justified that a notary certified consent of one of the spouses to the other spouse entering into civil agreements on acquiring corporate rights by means of investing marital property into the authorized share capital of a corporation serves as proof of being fully aware of the transfer of marital property. The discussed above notary certified consent reduces the risk of contracts on marital property transfer being voided by court.
Вінтоняк Н. Д. Набуття корпоративних прав одним із подружжя / Н. Д. Вінтоняк // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 42-47.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; корпоративні права подружжя; набуття корпоративних прав; юридична особа корпоративного типу; вклад; статутний капітал; право спільної сумісної власності; згода одного з подружжя; corporate rights of spouses; acquisition of corporate rights; corporation; predetermined contribution; authorized share capital; share in authorized capital; shared property rights